Pengaruh Jumlah Produksi Karet, Harga, dan Investasi Terhadap Volume Ekspor Karet Indonesia 1996 - 2010 - Wirawan, I Wayan Budi; Indrajaya, I Gusti Bagus (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 1, No. 2, Desember 2012, 2012)
This study aimed to determine the effect of the amount of production, prices, and investment to Indonesia rubber exports in 1996-2010, either simultaneously or partially. The analysis technique used is regeresi linear regression using the F test and t test .. The data analysis showed that the amount of production, prices and investment simultaneously significant effect on Indonesian rubber exports in 1996-2010. Partially only variable significant amount of production to Indonesia rubber exports in 1996-2010, while the price variable and the investment does not significantly influence the volume of rubber exports, Indonesia in 1996 - 2010.
Keywords: rubber exports , prices , investment , production quantities